2022
DOI: 10.1007/s11664-022-09431-y
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulant-Dependent Effects of Long-Term Low-Temperature Annealing on Interstitial Defects in Mg-Ion-Implanted GaN

Abstract: The encapsulant-dependent effects of long-term low-temperature annealing on defects in Mg-ion-implanted GaN have been investigated using metal-oxide-semiconductor (MOS) diodes. Annealing was carried out at 600 ℃ under nitrogen flow without or with a cap layer of Al2O3, SiO2, or SiN. For annealing at 600 ℃ for 3 h, the capacitance-voltage characteristics of the Al2O3 cap annealed samples indicated the existence of acceptor-like defects, whereas those of the capless, SiO2 cap and SiN cap annealed samples exhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 51 publications
(71 reference statements)
3
4
0
Order By: Relevance
“…Note that SiN-cap-annealed sample showed the highest N D -N A across the entire detection depth. This result is consistent with that of a previous study, 23) indicating that the Ga i diffusion during annealing at 600 °C was blocked by the SiN cap layer, resulting in the highest density of Ga i -related gap states in the vicinity of the Mg-implanted GaN surface. Even in the samples with other cap layers, the profiles should have been affected by the degree of Ga i diffusion into each cap layer.…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…Note that SiN-cap-annealed sample showed the highest N D -N A across the entire detection depth. This result is consistent with that of a previous study, 23) indicating that the Ga i diffusion during annealing at 600 °C was blocked by the SiN cap layer, resulting in the highest density of Ga i -related gap states in the vicinity of the Mg-implanted GaN surface. Even in the samples with other cap layers, the profiles should have been affected by the degree of Ga i diffusion into each cap layer.…”
Section: Resultssupporting
confidence: 93%
“…This is possibly because of the fact that the negatively charged N i defects increased in density in the vicinity of the GaN surface, as discussed in the previous work. 23) Although N i and Ga i can become mobile upon annealing at 600 °C, 22) it is unlikely that the V Ga V N defects diffuse at this temperature. 24) Indeed, upon annealing at 600 °C for 30 h, it has been confirmed that the Ga i defects diffused into the Al 2 O 3 cap layer, as shown in Table I and as described above.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations